Răspuns:
2. [tex]\left \{ {{y=-3+4*/x/ } \atop {-5*/x/+3y=5}} \right.[/tex]
[tex]-5*/x/+3(-3+4*/x/)=5[/tex]
Distribuim 3 elementelor din paranteza
[tex]-5*/x/-9+12*/x/=5[/tex]
[tex]7*/x/-9=5[/tex]
7*/x/=5+9
7*/x/=14
/x/=2
Modulul poate avea doua cazuri:
[tex]\left \{ {{x=2} \atop {x=-2}} \right.[/tex]
inlocuim valoarea lui x in ecuatia y=-3+4*/x/
[tex]\left \{ {{y=-3+4*/2/} \atop {y=-3+4*/-2/}} \right.[/tex]
[tex]\left \{ {{y=-3+4*2} \atop {y=-3+4*2}} \right.[/tex]
[tex]\left \{ {{y=-3+8} \atop {y=-3+8}} \right.[/tex]
[tex]\left \{ {{y=5} \atop {y=5}} \right.[/tex]
[tex]\left \{ {{x_{1},y_{1}=(2,5) } \atop {x_{2},y_{2}=(-2,5)}} \right.[/tex]